Oedipus of many pains - Barker, E; Christensen, J (University of Leeds, 2008)
In this paper we analyse Oedipus’ appearance during Odysseus’ tale in book 11 of Homer’s Odyssey in order to outline and test a methodology for appreciating the poetic and thematic implications of moments when ‘extraneous’ narratives or traditions appear in the Homeric poems. Our analysis, which draws on oral-formulaic theory, is offered partly as a re-evaluation of standard scholarly approaches that tend to over-rely on the assumed pre-eminence of Homeric narratives over other traditions in their original contexts or approaches that reduce such moments to instances of allusions to or parallels with fixed texts. In conjunction with perspectives grounded in orality, we emphasise the agonistic character of Greek poetry to explore the ways in which Odysseus’ articulation of his Oedipus narrative exemplifies an attempt to appropriate and manipulate a rival tradition in the service of a particular narrative’s ends. We focus specifically on the resonance of the phrases algea polla and mega ergon used by Odysseus as a narrator to draw a web of interconnections throughout Homeric and Archaic Greek poetry. Such an approach, in turn, suggests to what extent the Homeric Oedipus passage speaks to the themes and concerns of Homeric poetry rather than some lost Oedipal epic tradition and illustrates the importance of recognizing the deeply competitive nature of Homeric narratives vis-à-vis other narrative traditions.